Розвиток української освіти на Буковині та Закарпатті в кінці ХІХ - на початку ХХ ст. (Zaporizhzhia Historical Review, 2021)
Questions, related to the attempts to save the Ukrainian system of education in on territory of Western Ukraine, are examined in the article. The specific of Zakarpattya and Bukovina is determined. Statistical informationis given in relation to the different types of educational establishments.